Firefly Larva Feeding on Land Snails Ariophanta Cf. bajadera (Pfeiffer, 1850) and Tanychlamys pedina (Benson, 1865) in Maharashtra, India - Marathe, Aniket Dilip; Mahajan, Sharad (Journal of the Bombay Natural History Society (JBNHS), 2024)
No Abstract.